Method for determining fracture toughness of hard alloy
By combining the Mooney Rivlin model and cohesive model on the cemented carbide specimens, the accuracy problem of fracture toughness measurement of cemented carbide coatings in the prior art is solved, and higher accuracy calculation and verification are achieved.
Patent Information
- Application Number
- CN202411573041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The prior art is difficult to accurately measure the fracture toughness of cemented carbide coatings. The conventional testing steps are cumbersome and the results are affected by a variety of factors. Finite element simulation cannot accurately describe the awakening performance of the coating.
By preparing cemented carbide specimens, tensile mechanics experiments were performed to obtain elastic modulus and stress strain curves, the characteristics of the specimen were described in finite element simulation, and J-integral analysis was used to obtain type I and type II fracture energy, and the calculation results were verified through nano-indentation experiments and finite element simulations.
It improves the calculation accuracy of the fracture toughness of cemented carbide, can more accurately describe the fracture behavior and performance of the coating, and enhances the safety and reliability of the structure.
Smart Images

Figure CN119694437A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of cemented carbide performance testing, and in particular to a method for determining the fracture toughness of cemented carbide. Background Art
[0002] In recent years, physical vapor deposition (PVD) cemented carbide coatings have great potential for improving the surface performance of metal parts and extending their service life due to their excellent thermal stability, mechanical properties, oxidation resistance and corrosion resistance. However, the toughness of cemented carbide coatings is insufficient, and brittle peeling may occur during friction, causing the metal parts to gradually wear and fail. The lack of strength and toughness seriously restricts the application of cemented carbide coatings in extreme working conditions such as ocean, nuclear energy, and aerospace.
[0003] As one of the main parameters of the mechanical properties of cemented carbide materials, fracture toughness is an indicator of the material's ability to prevent crack propagation in the presence of cracks or similar defects. This ability can be described by parameters such as energy release rate, stress intensity factor, crack tip opening displacement (CTOD) and J integral. Materials with high fracture toughness can prevent or delay crack propagation when cracks occur, thereby improving the safety and reliability of the structure, which is crucial to ensuring the safe operation of important engineering structures. At present, the measurement of fracture toughness is generally obtained through experiments, but the conventional fracture toughness test test steps are relatively cumbersome and complicated, requiring sample preparation, fixture selection, displacement meter connection, loading, crack size measurement, and fracture toughness calculation. At the same time, the test results are affected by many factors, such as cross-sectional size, temperature, strain rate, etc.
[0004] The finite element method is used to determine the fracture toughness of cemented carbide coatings. At present, a numerical model has been established for related nanoindentation simulation. However, conventional simulation can only calculate the elastic properties of the film, such as hardness and elastic modulus, from the load-displacement curve, and cannot obtain information such as the film's recovery performance, making it difficult to reasonably determine the fracture toughness parameters of cemented carbide. Therefore, there are still major problems in the fracture simulation of cemented carbide coatings. Summary of the invention
[0005] The present invention provides a method for determining the fracture toughness of cemented carbide, which can improve the calculation accuracy of the fracture toughness. It includes: Prepare cemented carbide specimens, conduct tensile mechanical tests on the cemented carbide specimens, and obtain elastic modulus, Poisson's ratio and stress-strain curve of the cemented carbide specimens; The stress-strain value at the fracture point is selected from the stress-strain curve, and the maximum cohesion is calculated based on the fracture calculation formula and the stress-strain value; In the finite element simulation software, the Mooney Rivlin model and the cohesive force model are constructed to compositely describe the characteristics of the cemented carbide specimen; when the crack is not formed, the Mooney Rivlin model is used as the main constitutive model to describe the characteristics of the cemented carbide specimen; when the crack is formed, the cohesive force model is used as the main constitutive model to describe the characteristics of the cemented carbide specimen; The elastic modulus, Poisson's ratio and stress-strain curve are imported into the finite element simulation software, and models of multiple cemented carbide specimens with different fracture modes are constructed in the finite element simulation software. Based on the models of multiple cemented carbide specimens with different fracture modes, the J integral analysis is used to obtain the mode I fracture energy and the mode II fracture energy; The mode I fracture energy and mode II fracture energy are imported into the cohesive force model, and the nanoindentation uniaxial compression finite element numerical simulation is carried out in the finite element simulation software to obtain the simulated values of the stress-strain results. The nanoindentation experiment is carried out on the cemented carbide specimen to obtain the experimental values of the stress-strain results. According to the difference between the simulated value and the experimental value, the parameters in the finite element simulation analysis are adjusted, and the mode I fracture energy and mode II fracture energy are recalculated.
[0006] Optionally, the stress-strain value at the fracture point is selected in the stress-strain curve, and the maximum cohesion is calculated according to the fracture calculation formula and the stress-strain value, including: According to the stress-strain value at the fracture point, the fracture calculation formula is used. , calculate the maximum cohesion ,in, For cohesion, is the cohesive stiffness, is the crack tip opening displacement, is the critical displacement; in the process of calculating the maximum cohesion, the cohesion is divided into the normal stress value and the tangential stress values , the control equation is as follows: , ; in, is the maximum normal stress value, and the crack interface opening displacement value corresponding to the maximum normal stress value is ; is the maximum tangential stress value, and the crack interface opening displacement value corresponding to the maximum tangential stress value is ;Exceed The crack interface opening displacement corresponding to the stress value after ,Exceed The crack interface opening displacement corresponding to the stress value after .
[0007] Optionally, a Mooney Rivlin model and a cohesive force model of the cemented carbide specimen are constructed in the finite element simulation software to compositely describe the characteristics of the cemented carbide specimen, including: In the stage where cracks have not yet formed, the Mooney-Rivlin model is used as the main constitutive model for calculation, and the stress-strain relationship of the material is described by the strain energy density function. The strain energy density function is: After the crack is formed, the cohesive force model is used as the main constitutive model for calculation. It is assumed that there is a cohesive force region at the interface or crack tip. The stress-strain relationship of the material in the cohesive force region is different from that in other regions. By defining the constitutive relationship and damage evolution law of the cohesive force region, the interface debonding and crack propagation process are simulated.
[0008] Optionally, the elastic modulus, Poisson's ratio and stress-strain curve are imported into finite element simulation software, and models of multiple cemented carbide specimens with different fracture modes are constructed in the finite element simulation software. Based on the models of the cemented carbide specimens with multiple different fracture models, J-integral analysis is used to obtain the type I fracture energy and the type II fracture energy, including: According to linear elastic fracture mechanics, micro-column models of opening, sliding and tearing carbide specimens are established to calculate the stress-strain results of opening fracture, the stress-strain results of in-plane shear fracture and the stress-strain results of transverse shear fracture respectively. The angular variation of stress in the micro-pillar model of the cemented carbide specimens of the opening type, the sliding type, and the tearing type is obtained by combining the open fracture stress-strain results, the in-plane shear fracture stress-strain results, and the transverse shear fracture stress-strain results. The angular variation of stress in the micro-pillar model of the cemented carbide specimens of the opening type, sliding type, and tearing type is introduced into the partial derivative equation of the asymptotic solution at the crack tip, and the relationship between stress and angle and the distance from the integral position to the crack tip is obtained; The J-integral is performed according to the relationship between stress, angle, and the distance from the integral position to the crack tip to obtain the mode I fracture energy and mode II fracture energy.
[0009] Optionally, a uniaxial compression finite element numerical method of nanoindentation is performed in a finite element simulation software to obtain a simulated value of the stress-strain result, and a nanoindentation experiment is performed on a cemented carbide specimen to obtain an experimental value of the stress-strain result. According to the difference between the simulated value and the experimental value, the parameters in the finite element simulation analysis are adjusted, and the type I fracture energy and the type II fracture energy are recalculated, including: Importing mode I fracture energy and mode II fracture energy into the cohesion model in the finite element simulation software; In the finite element simulation software, a nanoindentation unidirectional compression finite element numerical simulation is performed on the model of the cemented carbide specimen to obtain a simulation value, and a nanoindentation experiment is performed on the cemented carbide specimen to obtain an experimental value. According to the size of the experimental value and the simulation value, the mesh size and the number of meshes in the finite element simulation software are adjusted; In the finite element simulation software, the model of the cemented carbide specimen is subjected to nanoindentation unidirectional compression finite element numerical simulation under different pressure conditions to obtain simulation values, and the cemented carbide specimen is subjected to nanoindentation experiment to obtain experimental values. According to the difference between the simulation value and the experimental value under different pressure conditions, the uncertainty parameters in the finite element simulation process are adjusted; The mode I fracture energy and mode II fracture energy are recalculated.
[0010] Optionally, in the finite element simulation software, a nanoindentation unidirectional compression finite element numerical simulation is performed on the model of the cemented carbide specimen to obtain a simulation value, and a nanoindentation experiment is performed on the cemented carbide specimen to obtain an experimental value, and the mesh size and the number of meshes in the finite element simulation software are adjusted according to the size of the experimental value and the simulation value, including: When the calculation time is too long, reduce the mesh size and the number of meshes; when the calculation simulation results are of low accuracy, encrypt the mesh of the fractured part, reduce the mesh size and increase the number of meshes.
[0011] Optionally, in the finite element simulation software, a nanoindentation unidirectional compression finite element numerical simulation is performed on the model of the cemented carbide specimen under different pressure conditions to obtain a simulation value, and a nanoindentation experiment is performed on the cemented carbide specimen to obtain an experimental value, and according to the difference between the simulation value and the experimental value under different pressure conditions, the uncertainty parameters in the finite element simulation process are adjusted, including: When the error between the simulation value and the experimental value under different pressure conditions exceeds the threshold, the uncertainty parameter influence analysis is performed on the uncertainty parameters in the finite element simulation process to evaluate the influence weight of the uncertainty parameters on the fracture toughness calculation results. The uncertainty parameters include the material parameters of the cemented carbide specimen, the geometric parameters of the cemented carbide specimen, and the loading conditions of the finite element simulation software. Adjust the uncertainty parameters according to the results of the uncertainty parameter impact analysis.
[0012] Optionally, a nanoindentation uniaxial compression finite element numerical simulation is performed on the model of the cemented carbide specimen under different pressure conditions to obtain simulation values, including: Finite element numerical simulation of nanoindentation uniaxial compression was performed with multiple pressure values at increments of 20 mN.
[0013] Optionally, the multiple pressure values in increments of 20 mN are 50 mN, 70 mN, 90 mN, 110 mN, 130 mN, 150 mN, 170 mN, 190 mN, and 210 mN respectively.
[0014] Optionally, the size of the mesh used in the finite element simulation is smaller than a size threshold, and the size threshold ranges from 0.3 to 0.7 μm.
[0015] The technical solution provided by the embodiments of the present disclosure has the following beneficial effects: In an embodiment of the present disclosure, a method for determining fracture toughness is provided. In the method steps, the Mooney Rivlin model and the cohesive force model are used in the finite element simulation software to compositely describe the characteristics of the cemented carbide specimen, wherein the Mooney Rivlin model can more accurately describe the characteristics of the cemented carbide specimen than the cohesive force model, and after the crack is formed, the fracture toughness (fracture energy) is calculated by the cohesive force model, thereby improving the calculation accuracy. In addition, after the fracture toughness is calculated, the type I fracture energy and the type II fracture energy are introduced into the cohesive force model, and a nanoindentation unidirectional compression finite element numerical simulation is performed in the finite element simulation software, and a nanoindentation experiment is performed on the cemented carbide specimen to verify whether the accuracy of the calculated fracture toughness meets the requirements. If it does not meet the requirements, the fracture toughness is calculated again after adjusting the parameters, thereby further improving the calculation accuracy of the fracture toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 A method flow chart of a method for determining the fracture toughness of a cemented carbide provided in an embodiment of the present disclosure; Figure 2 A schematic diagram of a plastic tensile specimen provided in an embodiment of the present disclosure; Figure 3 A schematic diagram of the tensile strength of a cemented carbide specimen provided in an embodiment of the present disclosure; Figure 4 A schematic diagram of an indentation test performed on a cemented carbide specimen provided in an embodiment of the present disclosure.
[0018] The reference numerals are as follows: 1: Plastic tensile specimen; 2: Cemented carbide specimen; 3: Nanoindenter. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Figure 1 A method flow chart of a method for determining the fracture toughness of a cemented carbide provided in an embodiment of the present disclosure. Figure 1 The method steps include: S11. Prepare a cemented carbide specimen, perform a tensile mechanics test on the cemented carbide specimen, and obtain the elastic modulus, Poisson's ratio, and stress-strain curve of the cemented carbide specimen.
[0021] In step S11, a cemented carbide coating (i.e., a cemented carbide specimen) is prepared on a plastic tensile specimen, and after the coating is prepared, the plastic substrate is melted under high temperature conditions, and the cemented carbide coating tensile specimen is retained, and an indoor tensile mechanics experiment is carried out to obtain the elastic modulus, Poisson's ratio, and stress-strain curve of the cemented carbide coating.
[0022] Among them, the dimensions of the cemented carbide specimens are those specified in the national standard GB / T 228.1-2021.
[0023] S12. Select the stress-strain value at the fracture point in the stress-strain curve, and calculate the maximum cohesion according to the fracture calculation formula and the stress-strain value.
[0024] In one example, step S12 includes: According to the stress-strain value at the fracture point, the fracture calculation formula is used. , calculate the maximum cohesion ,in, For cohesion, is the cohesive stiffness, is the crack tip opening displacement, is the critical displacement; in the process of calculating the maximum cohesion, the cohesion is divided into the normal stress value and the tangential stress values , the control equation is as follows: , ; in, is the maximum normal stress value, and the crack interface opening displacement value corresponding to the maximum normal stress value is ; is the maximum tangential stress value, and the crack interface opening displacement value corresponding to the maximum tangential stress value is ;Exceed The crack interface opening displacement corresponding to the stress value after ,Exceed The crack interface opening displacement corresponding to the stress value after .
[0025] In the embodiment of the present disclosure, when calculating the maximum cohesion, the cohesion is divided into normal stress and tangential stress, thereby further improving the calculation accuracy of the maximum cohesion.
[0026] In the disclosed embodiment, the calculation process applies the bilinear tension-displacement law to simplify the fracture behavior of the microcolumn into two linear stages: one is the elastic stage before reaching the yield point, when the deformation of the object is reversible, that is, the object can return to its original state after the external force is removed; the other is the plastic stage after reaching the yield point, when the object undergoes permanent deformation, and the deformation cannot be completely restored even if the external force is removed.
[0027] S13. In the finite element simulation software, the Mooney Rivlin model and the cohesive force model of the cemented carbide specimen are constructed to compositely describe the characteristics of the cemented carbide specimen. When the crack is not formed, the Mooney Rivlin model is used as the main constitutive model to describe the characteristics of the cemented carbide specimen. When the crack is formed, the cohesive force model is used as the main constitutive model to describe the characteristics of the cemented carbide specimen.
[0028] In one example, step S13 includes: In the stage where cracks have not yet formed, the Mooney-Rivlin model is used as the main constitutive model for calculation, and the stress-strain relationship of the material is described by the strain energy density function. The strain energy density function is: After the crack is formed, the cohesive force model is used as the main constitutive model for calculation. It is assumed that there is a cohesive force region at the interface or crack tip. The stress-strain relationship of the material in the cohesive force region is different from that in other regions. By defining the constitutive relationship and damage evolution law of the cohesive force region, the interface debonding and crack propagation process are simulated.
[0029] In the disclosed embodiment, the Mooney-Rivlin model and the cohesive force model are used to hybridly describe the stress-strain relationship of the material. The Mooney-Rivlin model describes the stress-strain relationship of the material through a strain energy density function, which is more conducive to improving the calculation accuracy of subsequent fracture toughness compared to the cohesive force model.
[0030] S14. Import the elastic modulus, Poisson's ratio and stress-strain curve into the finite element simulation software, construct models of multiple cemented carbide specimens with different fracture modes in the finite element simulation software, and use J-integral analysis to obtain type I fracture energy and type II fracture energy based on the models of the cemented carbide specimens with multiple different fracture models.
[0031] In one example, step S14 includes: In the first step, according to linear elastic fracture mechanics, micro-column models of opening, sliding and tearing carbide specimens are established, which are used to calculate the opening fracture stress-strain results, in-plane shear fracture stress-strain results and transverse shear fracture stress-strain results respectively.
[0032] Among them, the micro-column models of opening, sliding and tearing cemented carbide specimens are all constructed using the cohesive force model.
[0033] In the embodiment of the present disclosure, the size of the micro-column model is 8 μm×20 μm.
[0034] In the second step, the open fracture stress-strain results, in-plane shear fracture stress-strain results and transverse shear fracture stress-strain results are combined to obtain the angular change of stress of the micro-column model of the opening, sliding and tearing cemented carbide specimens.
[0035] In the third step, the angular variation of stress in the micro-pillar model of the opening, sliding and tearing cemented carbide specimens is introduced into the partial derivative equation of the asymptotic solution at the crack tip to obtain the relationship between stress and angle, and the distance from the integral position to the crack tip.
[0036] Among them, the partial derivative equation of the asymptotic solution at the crack tip is:
[0037] in, is the distance from the integration position to the crack tip, , is the Mode I (opening) stress intensity factor, is the Mode II (in-plane shear) stress intensity factor, is the Mode III (transverse shear) stress intensity factor. is the angular variation of stress for different cracking modes, obtained from finite element simulation. The fourth step is to perform J-integral based on the relationship between stress, angle, and the distance from the integral position to the crack tip to obtain mode I fracture energy and mode II fracture energy.
[0038] The definition of J integral is as follows:
[0039] in, is the strain energy density, is the tension vector on the crack boundary, is the displacement vector, is the path infinitesimal.
[0040] During the finite element analysis process, the J-integral value of the entire path can be obtained by integrating each unit on the integral path and then summing up. The post-processing function of the finite element simulation software can be used to extract the stress, strain, displacement and other data of each node on the path to calculate the integral, calculate the energy required for crack extension per unit area, and obtain the required Jc1 (Type I fracture energy) and Jc2 (Type II fracture energy).
[0041] S15. Import the type I fracture energy and type II fracture energy into the cohesive force model, perform nanoindentation uniaxial compression finite element numerical simulation in the finite element simulation software to obtain simulated values of stress-strain results, and perform nanoindentation experiments on cemented carbide specimens to obtain experimental values of stress-strain results. According to the difference between the simulated value and the experimental value, adjust the parameters in the finite element simulation analysis, and recalculate to obtain the type I fracture energy and type II fracture energy.
[0042] In one example, step S15 includes: Step 1: Import the mode I fracture energy and mode II fracture energy into the cohesion model in the finite element simulation software.
[0043] Step 2: In the finite element simulation software, perform nanoindentation unidirectional compression finite element numerical simulation on the model of the cemented carbide specimen to obtain simulation values, and perform nanoindentation experiment on the cemented carbide specimen to obtain experimental values. According to the size of the experimental value and the simulation value, adjust the mesh size and the number of meshes in the finite element simulation software.
[0044] In one example, step 2 includes: When the calculation time is too long, reduce the mesh size and the number of meshes; when the calculation simulation results are of low accuracy, encrypt the mesh of the fractured part, reduce the mesh size and increase the number of meshes.
[0045] Since the fracture simulation is performed by presetting cracks, stress concentration will occur at the crack tip. When the mesh is close to the crack tip, the stress-strain gradient is large. It is necessary to refine the finite element mesh near the crack tip. The finite element simulation model is used to carry out finite element numerical simulation of nanoindentation unidirectional compression of cemented carbide coating. The numerical simulation results are compared with the experimental results to compare the accuracy of the finite element simulation results, and the optimal mesh size and number are optimized. When the calculation time is too long, the mesh size and number are reduced. When the calculation simulation results are of low accuracy, the mesh of the fractured part is encrypted, the mesh size is reduced, and the mesh number is increased.
[0046] Step 3, in the finite element simulation software, perform nanoindentation unidirectional compression finite element numerical simulation on the model of the cemented carbide specimen under different pressure conditions to obtain simulation values, and perform nanoindentation experiments on the cemented carbide specimen to obtain experimental values, and adjust the uncertainty parameters in the finite element simulation process according to the difference between the simulation value and the experimental value under different pressure conditions.
[0047] In one example, step 3 includes: In the first step, when the error between the simulation value and the experimental value under different pressure conditions exceeds the threshold, the uncertainty parameter influence analysis is performed on the uncertainty parameters in the finite element simulation process to evaluate the influence weight of the uncertainty parameters on the fracture toughness calculation results. The uncertainty parameters include the material parameters of the cemented carbide specimen, the geometric parameters of the cemented carbide specimen, and the loading conditions of the finite element simulation software.
[0048] In the disclosed embodiment, the finite element numerical simulation of nanoindentation uniaxial compression is performed with multiple pressure values in increments of 20 mN. The accuracy of the finite element numerical simulation of nanoindentation uniaxial compression can be ensured by using 20 mN as an increment.
[0049] In the embodiment of the present disclosure, the multiple pressure values in increments of 20 mN are 50 mN, 70 mN, 90 mN, 110 mN, 130 mN, 150 mN, 170 mN, 190 mN, and 210 mN respectively.
[0050] The second step is to adjust the uncertainty parameters according to the results of the uncertainty parameter impact analysis.
[0051] In the disclosed embodiment, the influence weight of the uncertainty parameter on the calculation result of the fracture toughness is evaluated through uncertainty parameter impact analysis, so as to adjust the uncertainty parameter and further improve the calculation accuracy of the fracture toughness.
[0052] Nanoindentation experiments and corresponding finite element numerical simulations under different pressures were carried out using a nanoindenter. The simulated values were compared with the test values to verify the effectiveness of the determination method. When the error between the simulated stress-strain results and the test stress-strain values exceeded 5%, the uncertainties in the finite element simulation calculation process were changed, such as the uncertainty of material parameters (corrections were made for the thermal effects of the cemented carbide coating during the processing, changes in element content, and the influence of the coating structure on the mechanical properties of the material), errors in geometric shape (surface defects in the coating during the preparation process, etc., and the finite element calculation simulation model was corrected according to the actual micro-column morphology), changes in loading conditions (in the actual loading process, there were partial errors in the mechanical loading, and the finite element simulation boundary conditions were corrected and adjusted according to the actual force size and loading speed of the loading process), etc., and the influence analysis of the uncertainty parameters was performed to evaluate the influence weights of the relevant factors on the calculation results of the fracture toughness of the cemented carbide coating, so as to further improve the reliability and accuracy of the method of the present invention.
[0053] In the embodiment of the present disclosure, the size of the grid used in the finite element simulation is smaller than the size threshold, and the value range of the size threshold is 0.3-0.7 μm. For example, the size threshold is 0.5 μm.
[0054] In the embodiments of the present disclosure, using a grid of the above size is beneficial to ensuring calculation accuracy and calculation speed.
[0055] Step 4, recalculate the mode I fracture energy and mode II fracture energy.
[0056] In an embodiment of the present disclosure, a method for determining fracture toughness is provided. In the method steps, the Mooney Rivlin model and the cohesive force model are used in the finite element simulation software to compositely describe the characteristics of the cemented carbide specimen, wherein the Mooney Rivlin model can more accurately describe the characteristics of the cemented carbide specimen than the cohesive force model, and after the crack is formed, the fracture toughness (fracture energy) is calculated by the cohesive force model, thereby improving the calculation accuracy. In addition, after the fracture toughness is calculated, the type I fracture energy and the type II fracture energy are introduced into the cohesive force model, and a nanoindentation unidirectional compression finite element numerical simulation is performed in the finite element simulation software, and a nanoindentation experiment is performed on the cemented carbide specimen to verify whether the accuracy of the calculated fracture toughness meets the requirements. If it does not meet the requirements, the fracture toughness is calculated again after adjusting the parameters, thereby further improving the calculation accuracy of the fracture toughness.
[0057] Figure 2 A schematic diagram of a plastic tensile specimen provided by an embodiment of the present disclosure. Figure 2 , Figure 2The length, width and thickness of the plastic tensile specimen 1 are shown in FIG. The length is 190 mm, the width is 30 mm, and the thickness is 0.7 mm. The cemented carbide specimen is prepared on the plastic tensile specimen 1.
[0058] The above dimensions are merely examples provided in the present disclosure and are not intended to limit the present disclosure.
[0059] Figure 3 A schematic diagram of the tensile strength of a cemented carbide specimen provided in an embodiment of the present disclosure. Figure 3 The direction of the force applied during the tensile test is shown in Figure 3 The direction of the arrow in represents the direction of the force exerted on the cemented carbide specimen 2.
[0060] Figure 4 A schematic diagram of a cemented carbide specimen provided in an embodiment of the present disclosure undergoing an indentation test. Figure 4 , pressure is applied to the cemented carbide specimen 2 through the nano-indenter 3, and the direction of the arrow indicates the direction of the applied pressure.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for determining the fracture toughness of a cemented carbide, characterized in that: include: Prepare cemented carbide specimens, conduct tensile mechanical tests on the cemented carbide specimens, and obtain elastic modulus, Poisson's ratio and stress-strain curve of the cemented carbide specimens; The stress-strain value at the fracture point is selected from the stress-strain curve, and the maximum cohesion is calculated based on the fracture calculation formula and the stress-strain value; In the finite element simulation software, the Mooney Rivlin model and the cohesive force model are constructed to compositely describe the characteristics of the cemented carbide specimen; when the crack is not formed, the Mooney Rivlin model is used as the main constitutive model to describe the characteristics of the cemented carbide specimen; when the crack is formed, the cohesive force model is used as the main constitutive model to describe the characteristics of the cemented carbide specimen; The elastic modulus, Poisson's ratio and stress-strain curve are imported into the finite element simulation software, and models of multiple cemented carbide specimens with different fracture modes are constructed in the finite element simulation software. Based on the models of multiple cemented carbide specimens with different fracture modes, the J integral analysis is used to obtain the mode I fracture energy and the mode II fracture energy; The mode I fracture energy and mode II fracture energy are imported into the cohesive force model, and the nanoindentation uniaxial compression finite element numerical simulation is carried out in the finite element simulation software to obtain the simulated values of the stress-strain results. The nanoindentation experiment is carried out on the cemented carbide specimen to obtain the experimental values of the stress-strain results. According to the difference between the simulated value and the experimental value, the parameters in the finite element simulation analysis are adjusted, and the mode I fracture energy and mode II fracture energy are recalculated.
2. The method for determining the fracture toughness of cemented carbide according to claim 1, characterized in that: Select the stress-strain value at the fracture point in the stress-strain curve, and calculate the maximum cohesion according to the fracture calculation formula and the stress-strain value, including: According to the stress-strain value at the fracture point, the fracture calculation formula is used. , calculate the maximum cohesion ,in, For cohesion, is the cohesive stiffness, is the crack tip opening displacement, is the critical displacement; in the process of calculating the maximum cohesion, the cohesion is divided into the normal stress value and the tangential stress values , the control equation is as follows: , ; in, is the maximum normal stress value, and the crack interface opening displacement value corresponding to the maximum normal stress value is ; is the maximum tangential stress value, and the crack interface opening displacement value corresponding to the maximum tangential stress value is ;Exceed The crack interface opening displacement corresponding to the stress value after ,Exceed The crack interface opening displacement corresponding to the stress value after .
3. The method for determining the fracture toughness of cemented carbide according to claim 1, characterized in that: The Mooney Rivlin model and cohesive force model of the cemented carbide specimen are constructed in the finite element simulation software to compositely describe the characteristics of the cemented carbide specimen, including: In the stage where cracks have not yet formed, the Mooney-Rivlin model is used as the main constitutive model for calculation, and the stress-strain relationship of the material is described by the strain energy density function. The strain energy density function is: After the crack is formed, the cohesive force model is used as the main constitutive model for calculation. It is assumed that there is a cohesive force region at the interface or crack tip. The stress-strain relationship of the material in the cohesive force region is different from that in other regions. By defining the constitutive relationship and damage evolution law of the cohesive force region, the interface debonding and crack propagation process are simulated.
4. The method for determining the fracture toughness of cemented carbide according to claim 1, characterized in that: The elastic modulus, Poisson's ratio and stress-strain curve were imported into the finite element simulation software. Models of cemented carbide specimens with multiple different fracture modes were constructed in the finite element simulation software. Based on the models of cemented carbide specimens with multiple different fracture modes, the J integral analysis was used to obtain the type I fracture energy and type II fracture energy, including: According to linear elastic fracture mechanics, micro-column models of opening, sliding and tearing carbide specimens are established to calculate the stress-strain results of opening fracture, the stress-strain results of in-plane shear fracture and the stress-strain results of transverse shear fracture respectively. The angular variation of stress in the micro-pillar model of the cemented carbide specimens of the opening type, the sliding type, and the tearing type is obtained by combining the open fracture stress-strain results, the in-plane shear fracture stress-strain results, and the transverse shear fracture stress-strain results. The angular variation of stress in the micro-pillar model of the cemented carbide specimens of the opening type, sliding type, and tearing type is introduced into the partial derivative equation of the asymptotic solution at the crack tip, and the relationship between stress and angle and the distance from the integral position to the crack tip is obtained; The J-integral is performed according to the relationship between stress, angle, and the distance from the integral position to the crack tip to obtain the mode I fracture energy and mode II fracture energy.
5. The method for determining the fracture toughness of cemented carbide according to claim 1, characterized in that: The finite element simulation software is used to perform nanoindentation uniaxial compression finite element numerical simulation to obtain the simulated value of stress-strain results, and the cemented carbide specimen is subjected to nanoindentation experiment to obtain the experimental value of stress-strain results. According to the difference between the simulated value and the experimental value, the parameters in the finite element simulation analysis are adjusted, and the type I fracture energy and type II fracture energy are recalculated, including: Importing mode I fracture energy and mode II fracture energy into the cohesion model in the finite element simulation software; In the finite element simulation software, a nanoindentation unidirectional compression finite element numerical simulation is performed on the model of the cemented carbide specimen to obtain a simulation value, and a nanoindentation experiment is performed on the cemented carbide specimen to obtain an experimental value. According to the size of the experimental value and the simulation value, the mesh size and the number of meshes in the finite element simulation software are adjusted; In the finite element simulation software, the model of the cemented carbide specimen is subjected to nanoindentation unidirectional compression finite element numerical simulation under different pressure conditions to obtain simulation values, and the cemented carbide specimen is subjected to nanoindentation experiment to obtain experimental values. According to the difference between the simulation value and the experimental value under different pressure conditions, the uncertainty parameters in the finite element simulation process are adjusted; The mode I fracture energy and mode II fracture energy are recalculated.
6. The method for determining the fracture toughness of cemented carbide according to claim 5, characterized in that: In the finite element simulation software, the model of the cemented carbide specimen is subjected to nanoindentation unidirectional compression finite element numerical simulation to obtain simulation values, and the cemented carbide specimen is subjected to nanoindentation experiment to obtain experimental values. According to the size of the experimental value and the simulation value, the mesh size and the number of meshes in the finite element simulation software are adjusted, including: When the calculation time is too long, reduce the mesh size and the number of meshes; when the calculation simulation results are of low accuracy, encrypt the mesh of the fractured part, reduce the mesh size and increase the number of meshes.
7. The method for determining the fracture toughness of cemented carbide according to claim 5, characterized in that: In the finite element simulation software, the model of the cemented carbide specimen is subjected to nanoindentation unidirectional compression finite element numerical simulation under different pressure conditions to obtain simulation values, and the cemented carbide specimen is subjected to nanoindentation experiment to obtain experimental values. According to the difference between the simulation value and the experimental value under different pressure conditions, the uncertainty parameters in the finite element simulation process are adjusted, including: When the error between the simulation value and the experimental value under different pressure conditions exceeds the threshold, the uncertainty parameter influence analysis is performed on the uncertainty parameters in the finite element simulation process to evaluate the influence weight of the uncertainty parameters on the fracture toughness calculation results. The uncertainty parameters include the material parameters of the cemented carbide specimen, the geometric parameters of the cemented carbide specimen, and the loading conditions of the finite element simulation software. Adjust the uncertainty parameters according to the results of the uncertainty parameter impact analysis.
8. The method for determining the fracture toughness of cemented carbide according to claim 6, characterized in that: The simulation values are obtained by performing nanoindentation uniaxial compression finite element numerical simulation on the model of cemented carbide specimen under different pressure conditions, including: Finite element numerical simulation of nanoindentation uniaxial compression was carried out with multiple pressure values at increments of 20 mN.
9. The method for determining the fracture toughness of cemented carbide according to claim 8, characterized in that: The multiple pressure values in increments of 20 mN are 50 mN, 70 mN, 90 mN, 110 mN, 130 mN, 150 mN, 170 mN, 190 mN, and 210 mN respectively.
10. The method for determining the fracture toughness of cemented carbide according to claim 1, characterized in that: The size of the mesh used in the finite element simulation is smaller than the size threshold, and the size threshold ranges from 0.3 to 0.7 μm.
Citation Information
Patent Citations
Refractory material fracture parameter optimization method, system and device and medium
CN110032765A
Ball indentation characterization method for Mullins effect parameters
CN111044394A
Passivation line equation analysis method for elastic-plastic fracture toughness test
CN112098208A
Improved Beremin model parameter calibration method
CN113295564A
Method and device for acquiring interface fracture toughness based on splitting test and inversion algorithm
CN117313493A